The role of phytoconstituents in health care : biocompounds in medicinal plants - Goyal, Megh Raj; Suleria, Hafiz; Harikrishnan, Ramasamy (Palm Bay, Florida, USA : Apple Academic press, 2020)
"This new volume provides new insights with scientific evidence on the uses of medicinal plants in the treatment of certain diseases. It reviews various therapies with herbal phytoconstituents for certain types of disorders, modes of action, and pharmacological screening. It focuses on potential benefits of herbal extracts and bioactive compounds for human health care, provides a comparative phytoconstituent analysis of selected medicinal plants using GC-MS/FTIR techniques, and discusses the role of herbal medicines in female genital infections. It goes on to look at the health-boosting properties of cabbage and the functional properties of milk yam (Ipomoea digitata L.). The information provided in The Role of Phytoconstitutents in Health Care: Biocompounds in Medicinal Plants will be valuable for herbal drug researchers and scientists in the pharmaceutical industries. It will not only provide information on the management and prevention of HIV/AIDS and cancer disorders but will also pave the way for future research"--
Potential of Herbal Extracts and Bioactive Compounds for Human Healthcare / Ramasamy Harikrishnan and Chellam Balasundaram -- Herbal Extracts and Their Bioactivities: Comparative Phytoconstituent Analysis of Selected Medicinal Plants Using GC-MS/FTIR Techniques / C. Stanley Okereke, O. Uche Arunsi, E. Martina Ilondu, and S. Chieme Chukwudoruo -- The Role of Herbal Medicines in Female Genital Infections / Djadouni Fatima -- From Designer Food Formulation to Oxidative Stress Mitigation: Health-Boosting Constituents of Cabbage / Faiza Ashfaq, Masood Sadiq Butt, Ahmad Bilal, Kanza Aziz Awan, and Hafiz Ansar Rasul Suleria -- Functional Properties of Milk Yam (Ipomoea digitata L.) / K. M. Vidya, N. S. Sonia, and P. C. Jessykutty.
OCLC-licensed vendor bibliographic record.
Keywords: Herbs -- Therapeutic use; Medicinal plants; Cabbage -- Therapeutic use; TECHNOLOGY / Food Science